PERSONAL PROFILE AND SOCIAL ORIENTATIONS IN THE INTERPERSONAL RELATIONSHIPS AMONG STUDENTS IN THE FIELD OF HEALTH CARE - M. Bacheva (Trakia Journal of Sciences)
The PURPOSE of this study is to investigate the level of assertive behavior and selfesteem in students, teaching nurses and midwives, and to shape their personal profile and social orientations in interpersonal relationships. MATERIAL and METHODS: Were investigated 44 students studying in the nursing and midwifery profession for the level of the assertiveness and the behavior in interpersonal relationships. The research was carried out by a test method, with the following questionnaires specifically applied: Personality scale for the study of assertiveness- J. Tindall, Scale for the study of global self-esteem"- M. Rozenberg, Test for interpersonal relationships- T. Leary, were also studied. RESULTS: The results do not differ statistically significant from the normative sample, i.e. students studying to be nurses and midwives randomized to participate in this study demonstrated a level of assertiveness and self-esteem within the norm. However, there is a slight tendency for higher results in the group of midwives in terms of assertiveness and self-esteem. CONCLUSION: Students studying in both regulated professions should be encouraged to generate assertive skills. By establishing the characteristics of personality traits, which builds the profile of the medical specialist, can be considered as target units and stimulates appropriate socially significant orientation in behavior, corresponding to the needs of the two regulated professions.